(untitled) (The Pretoria Student Law Review, 2021)
Section 6 of the Constitution of the Republic of South Africa, 1996 recognises eleven official languages of the Republic and further requires the State to take practical steps to advance the use of African languages. The Statistics South Africa 2017/18 report shows that most South Africans’ first language are African languages. Despite this reality and the constitutional imperatives, the South African Bachelor of Laws (LLB) curriculum does not prescribe any African language as a compulsory course, and very few sources of law are in an African language. Some law schools do offer some African languages as an elective. However, it is submitted that this is not sufficient. Experience has shown that the inability to articulate oneself in English can be a barrier to completing the LLB degree in regulation-time and admission to legal practice. Furthermore, it is submitted that the Chief Justice 2017 Directive, in which Chief Justice Mogoeng declared English as the only language of record in South African courts, does not address the language problems experienced by court staff. Instead it simply perpetuates the Eurocentric legal system. This is because it counters the advancement and use of African languages envisaged by the Constitution. This article investigates how the failure to advance multilingualism in the current LLB curriculum can disadvantage law students going to practice. It is proposed that law schools begin to address this issue by introducing two innovations. First, it is suggested that law schools make at least one African language a compulsory course. For English first language speakers in particular, this arrangement will strengthen their understanding of the sociological context in which the law operates. Second, it is proposed that each law school should choose an African language that is predominantly spoken in their geographical area and partner with schools of languages to translate sources of law. For African first language speakers in particular, this will assist them in understanding legal concepts better. Translations of legal texts may also allow for law schools to teach the law in the local African language.